Cytotoxic lesions of the hippocampus increase social investigation but do not impair social-recognition memory. - Bannerman, D; Lemaire, M; Beggs, S; Rawlins, J; Iversen, S (2001)
A number of studies have implicated the hippocampal formation in social-recognition memory in the rat. The present study addressed this issue directly by assessing the effects of cytotoxic lesions confined to the hippocampus proper, encompassing the four CA subfields and the dentate gyrus, on this behavioural task. Ibotenate-induced hippocampal lesions led to locomotor hyperactivity and a marked spatial working-memory impairment on the elevated T-maze. In addition, they also led to increased social investigation. However, despite these clear effects, there was no effect of the lesions on social-recognition memory. These results suggest that the hippocampus proper does not subserve social-recognition memory; but does not, however, preclude the possibility that other areas of the hippocampal formation (e.g. entorhinal cortex or subiculum) may support this memory process.